2015
DOI: 10.1128/ec.00004-15
|View full text |Cite
|
Sign up to set email alerts
|

Eaf1 Links the NuA4 Histone Acetyltransferase Complex to Htz1 Incorporation and Regulation of Purine Biosynthesis

Abstract: Upon derepression, these poised nucleosomes respond rapidly to activate ADE gene expression in a mechanism likely reminiscent of the PHO5 promoter, leading to nucleosome disassembly. These detailed molecular events depict a specific case of cross talk between NuA4-dependent acetylation and incorporation of histone variant Htz1, presetting the chromatin structure over ADE promoters for subsequent chromatin remodeling and activated transcription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 50 publications
(85 reference statements)
1
19
0
Order By: Relevance
“…Upregulated genes common to previous eaf1 Δ transcriptome studies and our sec14-1 ts eaf1 Δ transcriptome included the stress response genes ( DDR2 , HSP12 , HSP26 ) (Lindstrom et al 2006; Cheng et al 2015). Together, these results indicate that deletion of EAF1 in the sec14-1 ts background impacts the transcriptome similar to what has been previously reported for NuA4 mutants in the wild-type background.…”
Section: Resultsmentioning
confidence: 99%
“…Upregulated genes common to previous eaf1 Δ transcriptome studies and our sec14-1 ts eaf1 Δ transcriptome included the stress response genes ( DDR2 , HSP12 , HSP26 ) (Lindstrom et al 2006; Cheng et al 2015). Together, these results indicate that deletion of EAF1 in the sec14-1 ts background impacts the transcriptome similar to what has been previously reported for NuA4 mutants in the wild-type background.…”
Section: Resultsmentioning
confidence: 99%
“…While the NuA4 complex was first demonstrated to be recruited to specific gene promoters, where it locally acetylates nucleosomal histones (9,14,15,18), more recent studies have shown that NuA4 is also present on actively transcribed coding sequences (open reading frames [ORFs]) (19,20). Its enrichment at promoters correlates with an increase of histone acetylation and chromatin relaxation, allowing access to DNA for the transcription machinery, and its targeting to promoters is thought to be mediated by transcription activators (13,15,21,31). However, NuA4 harbors several subunits carrying PTM-binding motifs (Fig.…”
mentioning
confidence: 99%
“…NuA4 acetylates lysines on the N-terminal tails of H4, H2A, and H2AZ (Htz1) histones (7,(9)(10)(11)(12), and its histone acetyltransferase (HAT) activity is important for the regulation of gene transcription (13)(14)(15)(16)(17)(18)(19)(20)(21) and also for the cellular response to DNA dam-age, recombination, and DNA double-strand break repair (22)(23)(24)(25)(26)(27). More recently, NuA4 was also shown to regulate life span and autophagy through its ability to acetylate nonhistone proteins (28)(29)(30).…”
mentioning
confidence: 99%
“…In yeast, certain groups of genes show high NuA4-dependence. These are mostly genes involved in translation and other anabolic processes 18,33,40,47,48 . Consistently, NuA4-defficient yeast strains are hypersensitive to rapamycin which inhibits growth-promoting TOR signaling 14 .…”
Section: Discussionmentioning
confidence: 99%